Role of Knowledge Management on the Influence of Total Quality Management on Organizational Performance - Khairul Bahrun; Hernadianto Hernadianto; Eti Arini; Rina Yuniarti; Ratna Wili (Journal of Social Science, 2021)
The purpose of the study was to analyze the effect of Total Quality Management on Organizational Performance mediated by Knowledge Management. This study used primary data in the form of a questionnaire to test hypotheses and analyzed using Structural Equation Modeling (SEM). The sample of this study amounted to 103 SMEs in Bengkulu City. The data analysis technique used WarpPLS version 6.0 software. The results showed that Total Quality Management had an effect on organizational performance and knowledge management did not mediate the effect of TQM on organizational performance.